Rol de la enfermera en pacientes que reciben hemodiálisis en el centro de diálisis contigo da vida del Club de Leones de la ciudad de Quevedo, provincia de Los Ríos, año 2012 - Morán Mindiola, Gasibe Matilde (2013)
This research was conducted in the dialysis center gives life Contigo Lions Club Quevedo city, located in the area Galo Plaza, across from City school Quevedo. The research had duration of 180 days and had as main objective to identify diagnoses and nursing role in renal failure patients undergoing hemodialysis. In total 40 patients of whom respondents chose the age range of 40-60 years, both male and female and nurses of the institution. The interview was made the Director of the Dialysis Center Lions Club Quevedo. In the field phase of the survey provided to patients undergoing hemodialysis is expressed that 60 % of patients treated at the dialysis center say that the treatment in the hospital setting is excellent , 28% said that is good and 12 % say it is regular. The 67.5 % of patients treated at the dialysis center say if they did a thorough examination during dialysis, while 22.5% say it made him a full examination, and 10 % have no opinion on the subject. 100 % of patients treated at the dialysis center say the nurse if they explained the care that must be followed. The 40 % of patients treated at the dialysis center say the quality of nursing service is good , 32% said it was very good , 20% expressed that is excellent and 8 % say it is regular care nurses . With respect to the results of surveys to nurses group Da Vida Contigo Clinic, all agreed that the patient weighed daily and checked vital signs and their respective record in the patient's medical history, considering also check sodium diet administration to the patient. In the interview with the Administrative Manager Dialysis Center was denoted that nurses are trained in their field of application, direct care with patients, and they have a manual, internal rules and protocols, just as their performance is evaluated within the unit.